Governance and financing of innovative very small business (VSB): evidence from a Canadian biotechnological firm. - Ouedraogo, Alidou (Economics and Business Review, 2017)
Using a very small business (VSB) as a starting point the aim of the paper is to show the extent to which substantial and rapid technological, institutional and competitive changes can affect the emergence of new innovative ideas. Moreover, the paper attempts to identify a few general areas worth contemplating regarding the mechanisms of governance and the financing of young, innovative companies that stem from this research. In sectors that are subject to rapid competitive and technological changes, the structure of governance, the financing and the implementation are all key elements to their success. Results based on a case study show three distinct governance structures with related financing strategies. Hence, the personally crafted governance is reflecting by a personal or proximity (family, friends) type of financing, professional governance is accompanying by government financing (federal and provincial) and governance growth relies on institutional financing.